Engineered Cancer Nanovaccines: A New Frontier in Cancer Therapy - Wang, Yijie; Liu, Congrui; Fang, Chao; Peng, Qiuxia; Qin, Wen; Yan, Xuebing; Zhang, Kun (Nano-Micro Letters, 2024)
Vaccinations are essential for preventing and treating disease, especially cancer nanovaccines, which have gained considerable interest recently for their strong anti-tumor immune capabilities. Vaccines can prompt the immune system to generate antibodies and activate various immune cells, leading to a response against tumor tissues and reducing the negative effects and recurrence risks of traditional chemotherapy and surgery. To enhance the flexibility and targeting of vaccines, nanovaccines utilize nanotechnology to encapsulate or carry antigens at the nanoscale level, enabling more controlled and precise drug delivery to enhance immune responses. Cancer nanovaccines function by encapsulating tumor-specific antigens or tumor-associated antigens within nanomaterials. The small size of these nanomaterials allows for precise targeting of T cells, dendritic cells, or cancer cells, thereby eliciting a more potent anti-tumor response. In this paper, we focus on the classification of carriers for cancer nanovaccines, the roles of different target cells, and clinically tested cancer nanovaccines, discussing strategies for effectively inducing cytotoxic T lymphocytes responses and optimizing antigen presentation, while also looking ahead to the translational challenges of moving from animal experiments to clinical trials. Highlights: 1 We classified the carriers that built cancer nanovaccines, discussed their diversified applications and coincidently compared their advantages and disadvantages. 2 Various cellular targets that guide the design and engineering of cancer nanovaccines are categorized and their characteristics and benefits are highlighted. 3 The clinical cases and encountered challenges in cancer nanovaccines are discussed, during which reasonable solutions and future research direction are provided.